Analisis Komparatif Struktur Data Array Dan Linked List; Evaluasi Performa Dan Implementasi Optimal - Arif Lukman SD; Gilang Arya S; Muhammad Putra I; Army Trilidia Devega (Riset Sinergi Indonesia (RISINDO), 2025)
Data structures are fundamental components in computer science that significantly impact program efficiency and performance. This study presents a comprehensive comparative analysis of two essential linear data structures: Array and Linked List. The research evaluates their characteristics, advantages, disadvantages, and optimal implementation scenarios through systematic performance testing and literature review managed using Zotero reference management system. Arrays provide contiguous memory allocation with O(1) random access but limited flexibility, while Linked Lists offer dynamic memory allocation with O(n) sequential access but greater structural flexibility. Results indicate that Arrays are optimal for applications requiring frequent data access and memory efficiency, whereas Linked Lists excel in scenarios with frequent structural modifications. This analysis provides practical guidelines for developers in selecting appropriate data structures based on specific application requirements.